“I was able to actually do something useful”: evaluating the experiences of university students after completing Mental Health First Aid: a mixed-methods study - Rodgers, Gina; Burns, Sharyn; Crawford, Gemma (2021)
Objective: Almost 50% of Australians will experience a mental health problem over their lifetime, with those aged 16–24 experiencing the highest prevalence. Among this group, university students have shown to be at higher risk compared to non-students. Mental Health First Aid (MHFA) was established to develop and enhance participant skills to respond appropriately to individuals experiencing mental health problems. This paper describes a mixed-method study measuring the long-term benefits of MHFA among students in a large Western Australian university.